2014
DOI: 10.1007/s12010-014-0731-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermokinetic Comparison of Trypan Blue Decolorization by Free Laccase and Fungal Biomass

Abstract: Free laccase and fungal biomass from white-rot fungi were compared in the thermokinetics study of the laccase-catalyzed decolorization of an azo dye, i.e., Trypan Blue. The decolorization in both systems followed a first-order kinetics. The apparent first-order rate constant, k1', value increases with temperature. Apparent activation energy of decolorization was similar for both systems at ∼ 22 kJ mol(-1), while energy for laccase inactivation was 18 kJ mol(-1). Although both systems were endothermic, fungal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
2
5
2
Order By: Relevance
“…It was also observed that the trypan blue dye was decolourized faster and better (65%) than the Congo red dye (28.85%) in the liquid media after 4 h of incubation. A similar percentage of decolourization of trypan blue dye was reported for a commercial laccase (62%) (Razak and Annuar, 2014), while 42% and 25% have been reported for laccase from Daedalea quercina and a marine fungus respectively (Baldrian., 2004;D'Souza et al, 2006). It has been established in a previous study that fungal biomass system and purified laccase could be applied in bio-decolourization processes (Razak and Annuar, 2014).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…It was also observed that the trypan blue dye was decolourized faster and better (65%) than the Congo red dye (28.85%) in the liquid media after 4 h of incubation. A similar percentage of decolourization of trypan blue dye was reported for a commercial laccase (62%) (Razak and Annuar, 2014), while 42% and 25% have been reported for laccase from Daedalea quercina and a marine fungus respectively (Baldrian., 2004;D'Souza et al, 2006). It has been established in a previous study that fungal biomass system and purified laccase could be applied in bio-decolourization processes (Razak and Annuar, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…A similar percentage of decolourization of trypan blue dye was reported for a commercial laccase (62%) (Razak and Annuar, 2014), while 42% and 25% have been reported for laccase from Daedalea quercina and a marine fungus respectively (Baldrian., 2004;D'Souza et al, 2006). It has been established in a previous study that fungal biomass system and purified laccase could be applied in bio-decolourization processes (Razak and Annuar, 2014). The use of the fungal biomass system implies the removal of dyes through their adsorption to the fungi mycelia or intracellular secretion of laccase which then aids in dye biodegradation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Immobilized laccase exhibited a strong decolorization capacity at short reaction times without mediator addition. Results significantly higher than those reported previously for Trypan Blue (Razak and Annuar, 2014), Bromothymol Blue (Ling et al, 2015) and Methyl Orange (Pardo et al, 2013) among others, showing the potential of immobilized biocatalyst developed.…”
Section: Decolorization Assayscontrasting
confidence: 52%
“…Laccase activity was measured according to Razak and Annuar (2014). The assay mixture contained 2.5 mL of phosphate-citrate buffer (0.1 M), 0.1 mL of syringaldazine (5 mM) and 0.5 mL of the enzyme solution.…”
Section: Methodsmentioning
confidence: 99%